Screening sumber cemaran bakteri pada kegiatan pemerahan susu di peternakan sapi perah rakyat Kabupaten Semarang - Prihutomo, Soni; Setiani, Bhakti Etza; Harjanti, Dian Wahyu (Faculty of Animal Science, Universitas Brawijaya, 2015)
The purpose of this experiment was to investigate the main source of bacteria contamination in milk at smallholder dairy farmers. The research was conducted at Margo Rukun dairy farm group in Semarang regency. Samples were milk and possible bacteria contamination sources during milking process such as: milk bucket swab, cow teat skin swab, farmer’s hand swab, water used during milking and napkin for wiping the udder (cutted at 1x1 cm square). Observed parameter was total number of bacteria using total plate count (TPC) method. The data were analyzed by t-test and linear regression analysis. The result showed that the total bacteria in milk were 320.143 CFU/ml. Total bacteria in the bucket (320.143 CFU/ml) was higher (p<0.05) than that in the water (149.227 CFU/ml). However, total bacteria in the water did not differ with the total bacteria in the teat skin (109.833 CFU/ml). Total bacteria in the teat skin were higher (p<0.05) than that in the napkin (96.750 CFU/ml) and in the farmer’s hands (33.380 CFU/ml). Highest coeficient correlation (r=0.384) was found between total bacteria in milk and total bacteria in milk bucket, indicating that the milk bucket gave the highest contribution to bacteria contamination in milk. Keywords: milk, bacteria, contamination, milking